Interrelationships of Economic Stressors, Mental Health Problems, Substance Use, and Intimate Partner Violence among Hispanic Emergency Department Patients: The Role of Language-Based Acculturation - Carol B. Cunradi (MDPI AG, 2021)
We analyzed the interrelationships of economic stressors, mental health problems, substance use, and intimate partner violence (IPV) among a sample of Hispanic emergency department patients and probed if Spanish language preference, which may represent low acculturation and/or immigrant status, had a protective effect, in accordance with the Hispanic health paradox. Study participants (n = 520; 50% female; 71% Spanish speakers) provided cross-sectional survey data. Gender-stratified logistic regression models were estimated for mental health problems (PTSD, anxiety, depression), substance use (risky drinking, cannabis, illicit drug use), and IPV. Results showed that economic stressors were linked with mental health problems among men and women. Among men, PTSD was associated with greater odds of cannabis and illicit drug use. Men who used cannabis and illicit drugs were more likely to report IPV. Male Spanish speakers had lower odds of anxiety and cannabis use than English speakers. Female Spanish speakers had lower odds of substance use and IPV than English speakers. The protective effect of Spanish language preference on some mental health, substance use, and IPV outcomes was more pronounced among women. Future research should identify the mechanisms that underlie the protective effect of Spanish language preference and explore factors that contribute to the observed gender differences.